Aruga mga sanaysay ng pagtanggap at paglingap - Rodriguez, Rommel B.; Jarin, Ferdinand P. (España, Manila, Philippines University of Santo Tomas Publishing House, 2022)
Gathers works of creative nonfiction from Filipino writers as they articulate the intimate, sometimes tough and agonizing ways that they express or receive “aruga” or care within the Filipino culture.
Introduksiyon -- Dear Awit / Dinah Palmera Pacquing Nadera -- Overnight sa Sementeryo / Beverly W. Siy -- Pusang Ama / Chuckberry J. Pascual -- Pihit / Emmanuel T. Barrameda -- Mga Liham Para sa Langit / Christopher Bryan Concha -- Keyboard at Breastfeed / Almayrah A. Tiburon -- Papa's Girl / Andyleen C. Feje -- Si Mang Jun / Ru Rui Perales -- Kapag Nawalan ng Papel ang Manunulat / Ansherina May D. Jazul -- Pagdating sa Dulo / Francisco Arias Montesena -- Tatlong Tala ng Isang Pseudo-Kuwentista / Napoleon I. Arcilla III -- Requerdos de Buhay / Mark Angeles -- MAMAmahayag / Che Sarigumba -- Sino siya? Mga Kabanata ng Pag-aruga / Heidi Emily Eusebio-Abad -- Dalawampu't Apat na Oras / Mubarak Tahir -- Parental Guidance / Christine Marie Lim Magpile -- Ang Paraiso nina Erning, Fely, at Nonong / Nonon Villaluz Carandang -- SepAnx / Joy Pye Cruz-Cadag -- Para kay Nanay Nieves / Marlon Lester -- Mga Tala Mula sa Mother Tree / Geraldine flores -- Mga Guhit Tungong Titik / Davidson L. Banquil -- Kung Paano ko Ginalugad ang Pagsulat sa Ilalim ng mga Talukap ni Ama at ni Ina / Mark Pornasdoro -- Faithful and Virtuous Night John Leihmar Toledo -- Tawag ng Tungkulin / Kimmy Baraoidan -- Batang-Nanay / Dolores R. Taylan -- Saynbord / Billy De Guzman -- Balanse / Geraldine Gentozala Juachon -- Ang Papa Kong Amoy Gasolina / Raymond Ybanez -- Elehiya / Jose Socrates Delos Reyes -- Para kay P / Catherine Anne B. Olivar -- Paskil / Manuelita Contreras-Cabrera -- Bilang Isang Anak / Yolanda G. Ealdama -- Senicide / Wilfredo Tabanera Jr. -- Sa Gunita ng Basag na Gitara / Joel Costa Malabanan -- Allison / Arthur David San Juan -- Sana Mahilig Magbasa ng Libro sina Mama at Papa / Jayson Fajardo -- Patsi-Patsing Danas sa Pangarap / Al Joseph Lumen.
Keywords: Filipino essays; Philippine essays (Filipino)